Functions of collocations in the prevention of linguistic errors among arabic learners as a foreign language - Abubakar Garba, Mahmud; Hassan, Abd Rauf; Abdul Jabar, Mohd Azidan (Taylor and Francis Group, 2023)
This research investigates the significance of collocations in preventing linguistic errors among undergraduates studying Arabic as a foreign language in Nigeria. For this purpose, a pre-experimental design was employed, wherein one group served as the pre-test and post-test measures. An intact class of 35 third-year undergraduate students, who were enrolled in essay writing at the Department of Arabic, 2022–2023 session, from Umaru Musa Yar’adua University, Katsina, Nigeria, were involved in the study, which lasted for a period of eleven sessions. The training session was based on a lexical approach. Therefore, essay writing was used to collect data after the treatment. The findings showed a significant increase in the mean score of the post-test. This implies that the incorporation of collocations in teaching Arabic to foreign language learners facilitated and motivated the participants to avoid linguistic errors. Therefore, this research suggests the integration of collocation in teaching Arabic to foreign language learners as an alternative writing method, especially in a Nigerian context. Furthermore, the research also offers theoretical and pedagogical implications and recommendations for future research.